A method for multiple solidification of nuclear waste using geopolymers

By adding magnesium additives and alkali exciters to the geological polymers, performing multiple grinding and calcining treatments to form a tight structure, the problem of low curing efficiency of geological polymers on anionic nuclides in the prior art is solved, and the nuclear is significantly improved The curing effect and stability of waste materials.

CN116375398BActive Publication Date: 2024-12-20CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310014046.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2024-12-20
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

The existing geological polymers have poor effect in curing radionuclides, especially the curing efficiency of anionic nuclides such as 79Se, and their structure is difficult to regulate during heat treatment, resulting in insufficient stability of radionuclides.

Method used

By mixing metakaolin, nuclear waste and magnesium additives with alkali exciter, grinding and calcining, a three-dimensional network structure is formed, and the solidification effect of nuclear waste is enhanced by calcining and remixing.

Benefits of technology

It significantly reduces the leaching rate of 137Cs, 90Sr and 79Se ions, improves the curing effect of nuclear waste, ensures higher safety and stability, and is suitable for safe landfill.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116375398B_ABST
    Figure CN116375398B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of radioactive hazardous waste treatment, and in particular to a method for multiple solidification of nuclear waste by geopolymers. The method comprises: S1. mixing metakaolin, nuclear waste, magnesium additives and alkali activators, grinding them together to obtain a primary mixed slurry, curing the primary mixed slurry until hardening, and obtaining a pre-solidified body; S2. crushing the pre-solidified body to a certain particle size, calcining it to obtain a calcined material; S3. mixing the calcined material with metakaolin, magnesium additives and alkali activators, grinding them again to obtain a secondary mixed slurry, curing the secondary mixed slurry until hardening, and obtaining a final solidified body of solidified nuclear waste. The solidified body is used for safe landfill. The method of the present invention can specifically regulate the in-situ structural transformation of geopolymers during the heat treatment process and enhance the solidification effect of radioactive nuclides.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of radioactive hazardous waste treatment, and in particular to a method for multiple solidification of nuclear waste using geopolymers. Background Art

[0002] Nuclear waste usually contains 137 Cs, 90 Sr. 60 Co. 129 I. 226 Ra, 79 Se and many other radionuclides. Near-surface burial disposal and deep geological disposal are currently the main methods for treating low- and medium-level radioactive waste and high-level radioactive waste respectively. Both require solidification treatment before burial. Geopolymers are three-dimensional inorganic polymer materials generated by a series of reactions such as depolymerization and condensation of silicon-aluminum-rich raw materials (such as kaolin) in a strong alkaline environment. They have very excellent mechanical properties and durability.

[0003] There have been many reports on the use of geopolymers in the immobilization of radionuclides, mainly focusing on 137 Cs, 90 Cationic nuclides such as Sr, the aluminum-oxygen tetrahedron in the geopolymer is negatively charged and can be 137 Cs + , 90 Sr 2+ However, the three-dimensional network structure of geopolymers has a certain degree of external penetration, and there is still a certain amount of 137 Cs + , 90 Sr 2+ The existing geopolymer curing effect needs to be enhanced. 79 Se oxygen-containing anions theoretically repel the remaining negative charges in the geopolymer structure, resulting in low anion curing efficiency of geopolymers, which limits the application of geopolymers in curing Se and other oxygen-containing anions.

[0004] Although the addition of other components can regulate the microstructure of geopolymers, such as patent CN115121575A discloses a method for preparing coal gangue-based active powder and solidifying the radionuclide Se, which uses the reducing property of divalent iron to reduce high-valence Se to low-valence to achieve stable solidification of Se, it still cannot change the disorder of the geopolymer structure and cannot achieve precise adaptation to the structure of the solidified radioactive nuclides.

[0005] Geopolymers have the possibility of structural transformation under the condition of external thermal field input due to their long-range disordered structure, realizing in-situ phase evolution. However, the main components of geopolymers are silicon and aluminum. The input of external thermal field provides the possibility of phase transformation, but it is impossible to achieve structural regulation. Therefore, how to regulate the in-situ structural transformation of geopolymers during the heat treatment process and enhance the curing effect of radionuclides is an unresolved technical problem. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a method for multiple solidification of nuclear waste by geopolymers, which can specifically regulate the in-situ structural transformation of geopolymers during the thermal treatment process and enhance the solidification effect of radioactive nuclides.

[0007] The present invention adopts the following technical solutions:

[0008] A method for multiple solidification of nuclear waste by geopolymers, wherein the nuclear waste is 137 Cs and / or 90 Sr waste, or the nuclear waste is containing 79 Se waste, comprising the following steps:

[0009] S1. Mixing metakaolin, nuclear waste, magnesium additive and alkali activator, grinding together to obtain a mixed slurry, curing the mixed slurry until hardened to obtain a pre-solidified body;

[0010] S2. After the pre-solidified body in S1 is crushed to a certain particle size, it is calcined to obtain a calcined material;

[0011] S3. The calcined material in S2 is mixed with kaolin, magnesium additive and alkali activator, and ground again to obtain a secondary mixed slurry, and the secondary mixed slurry is cured until hardened to obtain a final solidified body of solidified nuclear waste.

[0012] Preferably, in step S1, the alkali activator is a sodium silicate solution, and the modulus of the sodium silicate solution is 1.2; and the magnesium additive is magnesium oxide or magnesium hydroxide.

[0013] Preferably, in step S1, the metakaolin, nuclear waste and magnesium additive are mixed in a mass ratio of (70-85):(10-20):(5-10), and the mass ratio of the alkaline activator to the total material is 0.3-0.6;

[0014] Preferably, in step S1, the curing time is 3 to 7 days, and the material is cured until it is completely hardened.

[0015] Preferably, in step S2, the particle size of the crushing is determined according to the composition of the nuclear waste. 137 Cs and / or 90When the nuclear waste contains Sr, the crushing particle size is controlled at 3 to 6 cm; 79 Se, the crushing particle size is controlled above 6cm.

[0016] Preferably, in step S2, the calcination temperature is determined according to the composition of the nuclear waste. 137 Cs and / or 90 Sr, the calcination temperature is greater than 1000 ° C; when the nuclear waste contains 79 When Se is used, the calcination temperature is between 800 and 1000°C.

[0017] Preferably, in step S3, the metakaolin, calcined material and magnesium additive are mixed in a mass ratio of (30-40):(50-60):(5-10), and the mass ratio of the alkali activator to the total material is 0.3-0.6.

[0018] Preferably, in step S3, the curing time is 7 to 28 days, and the curing is performed until the compressive strength of the final solidified body is greater than 7 MPa.

[0019] The beneficial effects of the present invention are:

[0020] (1) After the nuclear waste is solidified once, it forms a pre-solidified body, namely, geopolymer. As an amorphous substance, geopolymer has a three-dimensional network space structure. 137 Cs, 90 Sr or 79 Se ions can be stored in its spatial network structure in the form of electrostatic force. The pre-solidified body is then crushed and calcined. After calcination, the three-dimensional network structure of the geopolymer will surround 137 Cs, 90 Sr or 79 The Se ions are transformed, making them more densely contained in the spatial structure of the calcined material, and the leaching rate of the ions is greatly reduced.

[0021] (2) To further reduce the risk of contact with the outside world, the dense structure of geopolymers is used to 37 Cs, 90 Sr or 79 The calcined material of Se ions is used as a geopolymer raw material to prepare a final solidified body for encapsulation, thereby realizing multiple solidification of nuclear waste. The prepared final solidified body can be used for safe landfill. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the process of the present invention;

[0023] Figure 2 The multiple solidification results of the Cs-containing nuclear waste in Example 1;

[0024] Figure 3 XRD patterns of geopolymers before and after calcination;

[0025] Figure 4 The multiple solidification results of nuclear waste containing Cs and Sr in Example 2;

[0026] Figure 5 This is the multiple solidification result of Se-containing nuclear waste in Example 3. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is described in more detail below in conjunction with the embodiments.

[0028] Example 1

[0029] like Figure 1 As shown, a method for multiple solidification of nuclear waste by geopolymers, wherein the nuclear waste contains 10% (by mass) 137 Cs waste, comprising the following steps:

[0030] S1. Mix kaolin, nuclear waste and magnesium oxide in a mass ratio of 7.5:2.0:0.5, and obtain a primary mixed slurry under the stimulation of an alkaline activator sodium silicate solution. The amount of sodium silicate solution is preferably a liquid-to-solid ratio of 0.6. The primary mixed slurry is cured for 3 days until it is completely hardened to obtain a pre-solidified body.

[0031] S2. The pre-solidified body in S1 was crushed to less than 5 cm, and then calcined at 1000°C for 2 h to obtain a calcined material.

[0032] S3. The calcined material in S2 is mixed with kaolin and magnesium oxide in a ratio of 5.5:3.5:0.5, and the mixture is ground again under the stimulation of an alkaline activator sodium silicate solution to obtain a secondary mixed slurry, wherein the amount of sodium silicate solution is preferably a liquid-to-solid ratio of 0.5, and the secondary mixed slurry is cured for 14 days to obtain a solidified slurry. 137 The final solidified body of Cs nuclear waste.

[0033] The modulus of the sodium silicate solution used above is 1.2.

[0034] The pre-solidified body (S1) obtained in S1, the calcined material (S2) in S2 and the final solidified body (S3) in S3 were subjected to leaching tests respectively, and the particle size was controlled to be between 3-5 mm, and the leaching solution was an acetic acid solution with a pH value of 2.88. The solid material and the leaching solution were mixed at a ratio of 20 kg:1 L, and shaken at a speed of 30 rpm for 18 hours, and then the leaching solution was collected to detect the Cs leaching concentration in each group of materials.

[0035] The leaching results are as follows Figure 2It can be seen that the leaching rate of S2 after calcination at 1000°C is much lower than that of the uncalcined pre-solidified body of S1, while the leaching rate of the final solidified body Cs of S3 after calcination and multiple solidification is further reduced, and the leaching concentration is only 0.002ppm, indicating an excellent solidification effect.

[0036] Analyze the XRD patterns of geopolymers before and after calcination, such as Figure 3 As shown, it can be clearly seen that the pre-solidified body (original sample) generates nepheline after calcination, which confirms that the geopolymer undergoes a phase transformation after calcination.

[0037] Example 2

[0038] A method for multiple solidification of nuclear waste by geopolymer, wherein the nuclear waste contains 15% (by mass) 137 Cs and 90 The waste of Sr comprises the following steps:

[0039] S1. Mix kaolin, nuclear waste and magnesium hydroxide in a mass ratio of 7.5:1.5:1.0, and obtain a primary mixed slurry under the stimulation of an alkaline activator sodium silicate solution. The amount of sodium silicate solution is preferably a liquid-to-solid ratio of 0.5. The primary mixed slurry is cured for 3 days until it is completely hardened to obtain a pre-solidified body.

[0040] S2. The pre-solidified body in S1 was crushed to less than 5 cm, and then calcined at 1000°C for 2.5 hours to obtain a calcined material.

[0041] S3. The calcined material in S2 is mixed with metakaolin and magnesium hydroxide in a ratio of 5.0:4.0:1.0, and the mixture is ground again under the stimulation of an alkaline activator sodium silicate solution to obtain a secondary mixed slurry, wherein the amount of sodium silicate solution is preferably a liquid-to-solid ratio of 0.5, and the secondary mixed slurry is cured for 28 days to obtain a solidified 137 Cs and 90 The final solidified body of Sr nuclear waste.

[0042] The modulus of the sodium silicate solution used above is 1.2.

[0043] The pre-solidified body (S1) obtained in S1, the calcined material (S2) in S2 and the final solidified body (S3) in S3 were subjected to leaching tests respectively, and the particle size was controlled to be between 3-6 mm, and the leaching solution was an acetic acid solution with a pH value of 2.88. The solid material and the leaching solution were mixed at a ratio of 20 kg:1 L, and shaken at a speed of 30 rpm for 18 hours, and then the leaching solution was collected to detect the leaching rates of Cs and Sr in each group of materials.

[0044] The leaching results are as follows Figure 4It can be seen that the leaching rate of S2 after calcination is much lower than that of the uncalcined pre-solidified body of S1, and the leaching rate of Cs and Sr in the final solidified body of S3 after calcination and multiple solidification is further reduced, and the leaching rate is less than 0.01%, and the solidification effect is excellent.

[0045] Example 3

[0046] A method for multiple solidification of nuclear waste by geopolymer, wherein the nuclear waste contains 5% (by mass) 79 Se waste, comprising the following steps:

[0047] S1. Mix kaolin, nuclear waste and magnesium oxide in a mass ratio of 7.0:2.0:1.0, and obtain a primary mixed slurry under the stimulation of an alkaline activator sodium silicate solution. The amount of sodium silicate solution is preferably a liquid-to-solid ratio of 0.6. The primary mixed slurry is cured for 7 days until it is completely hardened to obtain a pre-solidified body.

[0048] S2. The pre-solidified body in S1 is crushed to less than 6-9 cm, and then calcined at 800°C for 2h to obtain a calcined material.

[0049] S3. The calcined material in S2 is mixed with kaolin and magnesium oxide in a ratio of 5.5:3.5:1.0, and the mixture is ground again under the stimulation of an alkaline activator sodium silicate solution to obtain a secondary mixed slurry, wherein the amount of sodium silicate solution is preferably a liquid-to-solid ratio of 0.55, and the secondary mixed slurry is cured for 28 days to obtain a solidified slurry. 79 The final solidified body of Se nuclear waste.

[0050] The modulus of the sodium silicate solution used above is 1.2.

[0051] The pre-solidified body (without calcination) obtained in S1, the calcined material (calcined at 800°C) in S2 and the final solidified body in S3 were subjected to leaching tests respectively, and the particle size was controlled between 3 and 6 mm, and the leaching liquid was an acetic acid solution with a pH value of 2.88. The solid material and the leaching liquid were mixed at a ratio of 20 kg:1 L, and shaken at a speed of 30 rpm for 18 hours, after which the leaching solution was collected and the Se leaching rate in each group of materials was detected respectively.

[0052] The leaching results are as follows Figure 5 It can be seen that the leaching rate of S2 after calcination is much lower than that of the uncalcined pre-solidified body of S1, and the leaching rate of Se in the final solidified body of S3 after calcination and multiple solidification is further reduced, and the leaching rate is less than 0.05%, and the solidification effect is excellent.

[0053] The above implementation modes are only used to illustrate the technical solutions of the present invention, but not to limit the present invention. Although the present invention has been described in detail with reference to the above implementation modes, those skilled in the art should understand that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for multiple solidification of nuclear waste by geopolymers, wherein the nuclear waste is 137 Cs and / or 90 Sr waste, or the nuclear waste is containing 79 Se waste, characterized in that The following steps are involved: S1. The metakaolin, nuclear waste, magnesium additive and alkali activator are mixed and ground together to obtain a mixed slurry, and the mixed slurry is cured to harden to obtain a pre-solidified body; S2. After the pre-solidified body in S1 is crushed to a certain particle size, it is calcined to obtain a calcined material; S3. The calcined material in S2 is mixed with metakaolin, magnesium additive and alkali activator, and ground again to obtain a secondary mixed slurry, and the secondary mixed slurry is cured until hardened to obtain a final solidified body of solidified nuclear waste.

2. The method for multiple solidification of nuclear waste using geopolymers according to claim 1, characterized in that: In the step S1, the alkaline activator is a sodium silicate solution, and the modulus of the sodium silicate solution is 1.2; and the magnesium additive is magnesium oxide or magnesium hydroxide.

3. The method for multiple solidification of nuclear waste using geopolymers according to claim 2, wherein: In step S1, metakaolin, nuclear waste and magnesium additive are mixed in a mass ratio of (70-85):(10-20):(5-10), and the mass ratio of the alkali activator to the total material is 0.3-0.

6.

4. The method for multiple solidification of nuclear waste using geopolymers according to claim 1, wherein: In the step S1, the material is cured until it is completely hardened.

5. The method for multiple solidification of nuclear waste using geopolymers according to claim 1, wherein: In step S2, the particle size of the crushed material is determined according to the composition of the nuclear waste. 137 Cs and / or 90 When the nuclear waste contains Sr, the crushing particle size is controlled at 3 to 6 cm; 79 When Se, the crushing particle size is controlled above 6cm.

6. The method for multiple solidification of nuclear waste using geopolymers according to claim 1, characterized in that: In step S2, the calcination temperature is determined according to the composition of the nuclear waste. 137 Cs and / or 90 When the calcination temperature is greater than 1000 ° C. 79 When Se is used, the calcination temperature is between 800 and 1000°C.

7. The method for multiple solidification of nuclear waste using geopolymers according to claim 1, characterized in that: In step S3, the metakaolin, the calcined material and the magnesium additive are mixed in a mass ratio of (30-40):(50-60):(5-10), and the mass ratio of the alkali activator to the total material is 0.3-0.

6.

8. The method for multiple solidification of nuclear waste using geopolymers according to claim 1, characterized in that: In the step S3, the curing is performed until the final solidified body has a compressive strength greater than 7 MPa.